Crystal structure of diaqua-bis(1,10-phenanthroline κ2N,N′)nickel(II) trifluoroacetate- trifluoroacetic acid (1/1), C30H21F9N4NiO8 - Zhang Lan; Wang Qiang; Ding Wu-Xiu; Hao Hui-Min (Zeitschrift für Kristallographie - New Crystal Structures, 2019)
C30H21F9N4NiO8, monoclinic, P21/c (no. 13), a = 10.0630(11) Å, b = 9.625(1) Å, c = 18.196(2) Å, β = 116.10(3)°, V = 1582.7(5) Å3, Z = 2, Rgt(F) = 0.0511, wRref(F2) = 0.1261, T = 293(2) K.